Gender Differences in Atherosclerotic Vascular Disease: From Lipids to Clinical Outcomes - Vakhtangadze, Tamar; Singh Tak, Rajeeka; Singh, Utkarsh; Baig, Mirza S.; Bezsonov, Evgeny (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVDs) are one of the main reasons of death and morbidity in the world. Both women and men have high rates of cardiovascular morbidity and mortality, although gender-related differences in mortality and morbidity rates are observed in different age groups of the population. In the large cohort of cardiovascular disease, ischemic heart disease (IHD), heart failure (HF), systemic hypertension, and valvular heart disease are particularly common in the population. CVDs caused by atherosclerosis are in the first place in terms of frequency, that is why society is particularly interested in this problem. The development and course of atherosclerotic processes associated with lipid and other metabolic changes are characterized by a long latent period, the clinical manifestation is often an acute vascular catastrophe, which can lead to human disability and death. Differences associated with sex are observed in the clinical course and manifestations, which raises the suspicion that gender influences processes related to atherosclerosis. Atherosclerotic cardiovascular disease (ACD) includes two main most dangerous clinical manifestations: IHD and cerebrovascular disease (mainly ischemic stroke). Other less common clinical manifestations of atherosclerosis include aortic atherosclerosis and peripheral vascular disease. Gender-related differences were also identified concerning these diseases. The present review discusses the effects of gender and age on atherosclerotic processes, disease development, and clinical manifestations. The metabolic basis for the development of atherosclerosis appears to be related to sex hormones. Thus this issue is interesting and useful for doctors of different specialties.